Association of nonalcoholic fatty liver disease with subclinical myocardial remodeling and dysfunction: A population‐based study. Issue 3 (26th June 2015) - VanWagner, Lisa B.; Wilcox, Jane E.; Colangelo, Laura A.; Lloyd‐Jones, Donald M.; Carr, J. Jeffrey; Lima, Joao A.; Lewis, Cora E.; Rinella, Mary E.; Shah, Sanjiv J.
<x xml:space="preserve">Abstract</x> Nonalcoholic fatty liver disease (NAFLD) and heart failure (HF) are obesity‐related conditions with high cardiovascular mortality. Whether NAFLD is independently associated with subclinical myocardial remodeling or dysfunction among the general population is unknown. We performed a cross‐sectional analysis of 2, 713 participants from the multicenter, community‐based Coronary Artery Risk Development in Young Adults (CARDIA) study who underwent concurrent computed tomography (CT) quantification of liver fat and comprehensive echocardiography with myocardial strain measured by speckle tracking during the Year‐25 examination (age, 43‐55 years; 58.8% female and 48.0% black). NAFLD was defined as liver attenuation ≤40 Hounsfield units after excluding other causes of liver fat. Subclinical left ventricular (LV) systolic dysfunction was defined using values of absolute peak global longitudinal strain (GLS). Diastolic dysfunction was defined using Doppler and tissue Doppler imaging markers. Prevalence of NAFLD was 10.0%. Participants with NAFLD had lower early diastolic relaxation (e') velocity (10.8 ± 2.6 vs. 11.9 ± 2.8 cm/s), higher LV filling pressure (E/e' ratio: 7.7 ± 2.6 vs. 7.0 ± 2.3), and worse absolute GLS (14.2 ± 2.4% vs. 15.2 ± 2.4%) than non‐NAFLD (P < 0.0001 for all). When adjusted for HF risk factors or body mass index, NAFLD remained associated with subclinical myocardial remodeling and dysfunction (P < 0.01). The association of NAFLD with e' velocity (β = −0.36 [standard error = 0.15] cm/s; P = 0.02), E/e' ratio (β = 0.35 [0.16]; P = 0.03), and GLS (β = −0.42 [0.18]%; P = 0.02) was attenuated after controlling for visceral adipose tissue. Effect modification by race and sex was not observed. Conclusions: NAFLD is independently associated with subclinical myocardial remodeling and dysfunction and provides further insight into a possible link between NAFLD and HF. (Hepatology 2015;62:773–783)